Three-dimensional chitin-based scaffolds from Verongida sponges (Demospongiae: Porifera): part I, isolation and identification of chitin - Ehrlich, Hermann; Ilan, M.; Maldonado, M.; Muricy, G.; Bavestrello, G.; Kljajic, Z.; Carballo, J. L.; Schiaparelli, S.; Ereskovsky, A.; Schupp, P.; Born, R.; Worch, H.; et al. (International journal of biological macromolecules, 2010)
Marine invertebrate organisms including sponges (Porifera) not only provide an abundant source of biologically active secondary metabolites but also inspire investigations to develop biomimetic composites, scaffolds and templates for practical use in materials science, biomedicine and tissue engineering. Here, we presented a detailed study of the structural and physico-chemical properties of three-dimensional skeletal scaffolds of the marine sponges Aiolochroia crassa, Aplysina aerophoba, A. cauliformis, A. cavernicola, and A. fulva (Verongida: Demospongiae). We show that these fibrous scaffolds have a multilayered design and are made of chitin. 13C solid-state NMR spectroscopy, NEXAFS, and IR spectroscopy as well as chitinase digestion and test were applied in order to unequivocally prove the existence of α-chitin in all investigated species.